Preparation method of biodegradable polyester film special material and biodegradable polyester film special material

By adding auxiliary raw materials online to the polyester melt, the preparation process of biodegradable polyester film special materials is simplified, and the problems of complex process, high cost and unstable quality in the existing technology are solved, and high strength and stability are achieved Preparation of films.

CN119432013APending Publication Date: 2025-02-14CHINESE TEXTILE ACAD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310974263.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the process of preparing biodegradable polyester film special materials is complex, the production cost is high, and the product quality is unstable, resulting in insufficient film strength, which limits its application scenarios.

Method used

Using biodegradable polyester materials continuously prepared from monomer raw materials, the mixture is uniform and microcrosslinking and chain extension reactions are achieved by adding microcrosslinking agents, rigid-enhancing agents and functional masterbatches online to the polyester melt, thereby achieving uniform mixing and microcrosslinking and chain extension reactions. Improve the mechanical properties of the product.

Benefits of technology

The preparation process is simplified, costs are reduced, product quality stability is improved, high-strength biodegradable polyester film is realized, and its application scenarios are expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432013A_ABST
    Figure CN119432013A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a special material for a biodegradable polyester film and the special material for the biodegradable polyester film, the preparation method comprises the following steps: (1) mixing a mixture of terephthalic acid, aliphatic dibasic acid and butanediol with a catalyst to obtain a mixed slurry, the aliphatic dibasic acid being succinic acid or adipic acid; (2) carrying out esterification reaction on the mixed slurry to obtain an esterified material; (3) carrying out ester exchange reaction on the ester material to obtain an ester melt; (4) carrying out a pre-polycondensation reaction on the ester melt to obtain a pre-polycondensation product; (5) carrying out final polycondensation reaction on the pre-polycondensation product to obtain a polyester melt; and (6) in the discharging process of the polyester melt, adding the micro-crosslinking agent, the stiffening agent and the functional master batch on line, and extruding and granulating to obtain the polyester material. According to the preparation method, the polyester material capable of being directly used for film blowing can be continuously prepared from the monomer raw materials, the preparation process is simple, and the obtained product is stable in quality and suitable for stable production of film blowing manufacturers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biodegradable polyester preparation, and in particular relates to a preparation method of a special material for biodegradable polyester film and the special material for biodegradable polyester film. Background Art

[0002] Biodegradable polyester, such as polybutylene terephthalate-co-succinate (PBST) or polybutylene terephthalate-co-adipate (PBAT), is a new type of biodegradable polymer material, which has the characteristics of high strength, good blown film properties, and easy biodegradation, and is suitable for the preparation of agricultural mulch. Since this mulch is biodegradable, it does not need to be recycled, has a relatively small impact on the land, and can avoid the white pollution of the land caused by ordinary PE mulch.

[0003] In the prior art, when preparing special materials for biodegradable polyester films, pure biodegradable polyester, i.e., PBST resin or PBAT resin, is usually dried, mixed evenly with a stiffening agent and a mineral masterbatch, and then blown into a film to prepare a biodegradable polyester composite film. The above-mentioned preparation process requires the pure PBST resin or PBAT resin to be dried again, and needs to be mixed evenly with a stiffening agent and a mineral masterbatch, so the preparation process is relatively complicated and the production cost is slightly high. At the same time, the quality of products from different batches is prone to fluctuations, and the strength of the biodegradable polyester film prepared by subsequent blown film is not high, resulting in limited application occasions.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a special material for biodegradable polyester film and a special material for biodegradable polyester film, which can realize the continuous preparation of biodegradable polyester materials that can be directly used for blown film from monomer raw materials, while improving the mechanical properties of the product.

[0006] In order to solve the above technical problems, the basic concept of the technical solution adopted by the present invention is:

[0007] A method for preparing a biodegradable polyester film special material comprises the following steps:

[0008] (1) mixing a mixture of a dibasic acid and butanediol with a catalyst to obtain a mixed slurry, wherein the dibasic acid comprises terephthalic acid and an aliphatic dibasic acid, and the aliphatic dibasic acid is succinic acid or adipic acid;

[0009] (2) subjecting the mixed slurry to an esterification reaction to obtain an esterified material;

[0010] (3) the esterified material undergoes an ester exchange reaction to obtain an esterified melt;

[0011] (4) the esterification product melt is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product;

[0012] (5) subjecting the pre-polycondensation product to a final polycondensation reaction to obtain a polyester melt;

[0013] (6) During the polyester melt discharging process, auxiliary raw materials are added online and extruded into granules to obtain a biodegradable polyester film special material, wherein the auxiliary raw materials include a micro-crosslinking agent, a stiffening agent and a functional masterbatch.

[0014] In the present invention, a biodegradable polyester material that can be directly used for film blowing can be continuously prepared from monomer raw materials, and a micro-crosslinking agent, a stiffening agent and a functional masterbatch are added online to the polyester melt in a molten state. On the one hand, a series of complex preparation processes that require secondary drying of pure PBST resin or PBAT resin, melting and mixing with other materials that need to be added in the prior art are omitted. On the other hand, if auxiliary raw materials such as functional masterbatch are added in the polymerization reaction stage, it is usually difficult to prepare a high molecular weight polymer that meets the requirements of the film blowing grade. At the same time, the polycondensation reaction stage can only be stirred in the reactor, and the dispersion effect of the auxiliary raw materials is not very ideal. The scheme of the present invention has low energy consumption, low cost, high molecular weight, uniform dispersion, large output, good product quality stability, and is easy to realize large-scale industrial production. The obtained product is suitable for blowing high-strength biodegradable polyester film with stable quality.

[0015] Furthermore, in step (6), the polyester melt is subjected to a process of online addition of auxiliary raw materials and extrusion through a screw online adding device, wherein the screw extrusion temperature is 250-260° C., the screw speed is controlled to be 300-400 rpm, and the aspect ratio of the screw is 70-82:1;

[0016] Preferably, the screw extrusion temperature is 255-260° C., the screw speed is controlled to be 300-350 rpm, and the aspect ratio of the screw is 75-82:1.

[0017] Furthermore, in step (6), the mass ratio of the micro-crosslinking agent, the stiffening agent and the functional masterbatch is 1:1000-1200:2000-2500, and the mass ratio of the total mass of the auxiliary raw materials to the polyester melt is 1-2:9-20;

[0018] Preferably, the micro-crosslinking agent is a peroxide, including DCP or BIBP, preferably BIBP;

[0019] Preferably, the stiffening agent is polylactic acid, the molecular weight of which is preferably 200,000 to 250,000, and the melt index is preferably 10 to 15 g / 10 min;

[0020] Preferably, the functional masterbatch uses PBST or PBAT as a carrier, wherein the content of the functional powder is 70-75%; the melt index of the functional masterbatch is preferably 5-10g / 10min; the functional powder preferably comprises a mixture of nano-talc and nano-silicon dioxide in a mass ratio of 2-3:1.

[0021] The melt index is also called the melt index, which refers to the mass of the plastic melt passing through a standard die capillary every 10 minutes under a certain temperature and load.

[0022] In the above scheme, the polyester melt obtained by the final polycondensation reaction is added with micro-crosslinking agent, stiffening agent and functional masterbatch online during the discharging process, and it is easier to achieve uniform mixing of the polyester melt and the above auxiliary raw materials in the molten state, thereby ensuring that the obtained product has good mechanical properties. During the mixed extrusion process, the polyester melt further achieves micro-crosslinking and chain extension reactions, thereby obtaining a high-strength biodegradable polyester film special material with stable quality, and then the biodegradable polyester film made of this special material has higher tensile strength, expanding the subsequent application scenarios of the biodegradable polyester film.

[0023] Specifically, in the present invention, the discharge pipeline of the polyester melt is connected to a screw online adding device, and the screw online adding device is equipped with an online adding metering device. The auxiliary raw materials are quantitatively added to the screw online adding device through the online adding metering device, and are evenly mixed with the polyester melt through a dynamic mixer in the screw online adding device, and are finally extruded through a metering pump, air-cooled and pelletized, and packaged to obtain a special material for biodegradable polyester film.

[0024] More specifically, in the above scheme, the addition amount of the auxiliary raw material is 15-30 Kg / h, and the extrusion amount is 290-320 Kg / h.

[0025] Furthermore, in step (1) of the preparation method, a catalyst is added to the mixture of the dibasic acid and butanediol for pulping, and the pulping time is 20 to 30 minutes, preferably 20 to 25 minutes;

[0026] Preferably, the dibasic acid and butanediol are added to a pulping kettle at a molar ratio of 1:1.27-1.30 for pulping;

[0027] More preferably, in the dibasic acid, the molar ratio of terephthalic acid to aliphatic dibasic acid is 1:1.2-1.3.

[0028] Specifically, in the present invention, the terephthalic acid (PTA) is a white powder with a purity of 99.8% to 99.9% and a density of 1.51 g / cm 3The succinic acid and adipic acid are both white powders with a purity of 99.8% to 99.9%; the butanediol is a colorless liquid with a purity of 99.6% to 99.9% and a boiling point of 225 to 228°C.

[0029] Furthermore, the amount of the catalyst added is 0.01% to 0.03% by mass of terephthalic acid, preferably 0.02%;

[0030] Preferably, the catalyst is a mixture of zinc octoate and zinc chloride, wherein the molar ratio of zinc octoate to zinc chloride is 1:2 to 3; preferably 1:2 to 2.5.

[0031] In the above scheme, the dibasic acid as the monomer raw material is slurried with butanediol and the catalyst, so that various reaction raw materials and catalysts can be fully mixed and evenly mixed, which is beneficial to the subsequent esterification reaction. The mixed slurry obtained after the slurrying is transported to the slurry supply pipe for internal circulation, and the mixed slurry is quantitatively transported from the slurry supply tank to the equipment for the next reaction process.

[0032] Furthermore, in step (2), the reaction temperature for the esterification reaction is 145 to 165° C., preferably 155 to 165° C.; after the esterification rate of the esterification reaction reaches 50% to 55%, preferably 52% to 55%, the ester exchange reaction of step (3) is carried out;

[0033] Preferably, the mixed slurry is fed into the first esterification kettle for esterification reaction, and the flow rate of the mixed slurry entering the first esterification kettle is controlled at 160-180 Kg / h, preferably 165-175 Kg / h; the liquid level in the first esterification kettle is maintained at 600-800 mm.

[0034] Furthermore, in step (3), the reaction temperature for the transesterification reaction is 210 to 220° C., preferably 215 to 220° C.; after the transesterification rate of the transesterification reaction reaches 98% to 99.5%, preferably 98% to 99%, the pre-polycondensation reaction of step (4) is carried out;

[0035] Preferably, the esterified material is fed into the second esterification kettle for ester exchange reaction, and the flow rate of the esterified material entering the second esterification kettle is controlled at 170-180 Kg / h, preferably 175-180 Kg / h; the liquid level in the second esterification kettle is maintained at 600-800 mm.

[0036] Specifically, in the present invention, the mixed slurry in the slurry supply tank is pumped into the first esterification kettle at a flow rate of 160-180 kg / h for esterification reaction, and after the esterification rate reaches 50%-55%, it is pumped into the second esterification kettle at a flow rate of 170-180 kg / h for transesterification reaction. By performing two-step esterification, the reaction raw materials can be more fully reacted to form ester compounds.

[0037] Furthermore, in step (4), the melt temperature is controlled to be 245-255° C., and the pre-polycondensation reaction is carried out under a vacuum degree of 1000-1250 Pa, and the reaction time is 30-50 min; the vacuum degree is preferably 1200-1250 Pa;

[0038] Preferably, the esterification melt is fed into a pre-polycondensation kettle for pre-polycondensation reaction, and the liquid level in the pre-polycondensation kettle is controlled to be maintained at 540-560 mm;

[0039] More preferably, before the esterified product melt enters the pre-polycondensation reactor, a polycondensation catalyst is added to the esterified product melt, and the amount of the polycondensation catalyst added is 0.01% to 0.02% of the mass of terephthalic acid;

[0040] Further preferably, the polycondensation catalyst is a butanediol solution of titanium chloride, wherein the mass fraction of titanium chloride is 70% to 80%.

[0041] In the present invention, the amount of catalyst and polycondensation catalyst added is controlled according to the amount of terephthalic acid used, thereby avoiding the problem of error in calculation based on the total amount of dibasic acid. At the same time, the amount of catalyst and polycondensation catalyst added calculated in the above manner does not affect the quality of the final product.

[0042] Specifically, in the present invention, the esterified melt obtained in step (3) includes the esterification product of the esterification reaction in step (2) and the ester exchange product of the ester exchange reaction in step (3). The esterified melt is pumped into the melt pipeline through a metering pump, and the esterification product and the ester exchange product are mixed evenly through a pipeline homogenizer on the melt pipeline to prepare for the subsequent pre-polycondensation reaction. The polycondensation catalyst is metered into the melt pipeline through a pipeline injector, and the polycondensation catalyst is added upstream of the pipeline homogenizer, so that the polycondensation catalyst flows through the pipeline homogenizer and is mixed evenly with the esterified melt before entering the pre-polycondensation reactor.

[0043] The polycondensation catalyst is a butanediol solution of titanium chloride, wherein the titanium chloride is white powder with a purity of 99.5% to 99.9%; the butanediol solution of titanium chloride is white liquid with a mass concentration of 70% to 80%.

[0044] Furthermore, in step (5), the melt temperature is controlled to be 250-260° C., and the final polycondensation reaction is carried out under a vacuum degree of 50-100 Pa, and the reaction time is 30-40 min; the vacuum degree is preferably 50-80 Pa;

[0045] Preferably, the pre-polycondensation product enters the final polycondensation kettle for final polycondensation reaction, and the liquid level in the final polycondensation kettle is controlled to be maintained at 400-500 mm;

[0046] Preferably, the product of the final polycondensation reaction is detected online, and after the intrinsic viscosity reaches 1.250 to 1.350 dL / g, the polyester melt can be discharged in step (6).

[0047] In the above scheme, after the product of the final polycondensation reaction reaches a certain molecular weight, it can be discharged and mixed with the auxiliary raw materials for extrusion. For polymer compounds, there is a correlation between their molecular weight and intrinsic viscosity. By performing online detection of the intrinsic viscosity of the product of the final polycondensation reaction, the discharge timing of the polyester melt can be accurately controlled to ensure the micro-crosslinking and chain extension reaction effects in the subsequent mixing and extrusion process, without affecting the continuity of the overall preparation process.

[0048] The present invention also provides a special material for biodegradable polyester film, wherein the special material for biodegradable polyester film has a tensile strength of 30-35 MPa, an elongation at break of 800%-1000%, and a hardness of 60-70A;

[0049] Preferably, the special material for biodegradable polyester film is prepared by the preparation method of the special material for biodegradable polyester film described above.

[0050] The above-mentioned special material for biodegradable polyester film has high tensile strength, is suitable for the film blowing preparation process, can be used to prepare biodegradable polyester film with high strength, and is particularly suitable for preparing agricultural mulch film.

[0051] After adopting the above technical scheme, the present invention has the following beneficial effects compared with the prior art.

[0052] 1. Compared with the existing intermittent preparation method, the preparation method of the present invention can continuously prepare biodegradable polyester materials that can be directly used for film blowing from monomer raw materials, eliminating the cumbersome preparation process of first drying the pure resin and mixing it with other raw materials such as functional masterbatch, saving preparation costs and making the preparation process simpler.

[0053] 2. The quality of the prepared special material for biodegradable polyester film is more stable, which is suitable for stable production by blown film manufacturers. The special material has higher tensile strength, which is suitable for the blown film process, and can be made into a biodegradable polyester film with high tensile strength, which is conducive to expanding the subsequent application occasions of the biodegradable polyester film.

[0054] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] The accompanying drawings are part of the present invention and are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention, but do not constitute an improper limitation of the present invention. Obviously, the drawings described below are only some embodiments. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the accompanying drawings:

[0056] Figure 1 The present invention is a flow chart of the preparation process of the biodegradable polyester film special material.

[0057] It should be noted that these drawings and textual descriptions are not intended to limit the conceptual scope of the present invention in any way, but are intended to illustrate the concept of the present invention for those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION

[0058] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The following embodiments are used to illustrate the present invention but are not used to limit the scope of the present invention.

[0059] In order to realize the method for preparing the special material for biodegradable polyester film of the present invention, the following continuous polymerization and online addition production line is adopted in the embodiment of the present invention to continuously prepare the special material for biodegradable polyester film.

[0060] Specifically, Figure 1 As shown, the production line at least includes a pulping kettle, two esterification kettles, namely a first esterification kettle and a second esterification kettle, a pre-condensation kettle, a final condensation kettle, and a screw online adding device.

[0061] Among them, the reaction raw materials (including PTA, succinic acid or adipic acid, butanediol) and the catalyst for esterification reaction are added to the beating kettle for beating, and the resulting mixed slurry enters the first esterification kettle for esterification reaction. After the esterification reaches the requirements, it enters the second esterification kettle for transesterification reaction. The reaction product in the second esterification kettle is pumped into the pre-condensation kettle, and a certain amount of polycondensation catalyst is added to the melt pipeline before entering the pre-condensation kettle through a syringe. After flowing through the pipeline homogenizer and being evenly mixed, it enters the pre-condensation kettle for pre-condensation reaction. The pre-condensation kettle is specifically an upflow pre-condensation kettle. The pre-polycondensation product is pumped into the final polycondensation kettle for polycondensation reaction. After polycondensation to a certain molecular weight, the obtained polyester melt is discharged along the discharge pipeline to the screw online adding device. The micro-crosslinking agent, stiffening agent and functional masterbatch are quantitatively added to the polyester melt through the screw online adding device. After being uniformly mixed in the dynamic mixer in the screw online adding device, it is extruded through a metering pump and air-cooled and pelletized, thereby continuously preparing a biodegradable polyester film special material that can be directly used for film blowing.

[0062] Furthermore, the pre-polycondensation reactor and the final polycondensation reactor are both connected to a recovery system for recovering butanediol. In the above-mentioned continuous preparation process, butanediol that has not been completely reacted can also be recovered from the pre-polycondensation reactor and the final polycondensation reactor, and reused as a reaction raw material after purification, or used in other production processes that require the participation of butanediol.

[0063] Example 1

[0064] In this embodiment, the biodegradable polyester film is prepared according to the following steps:

[0065] (1) adding a mixture of PTA and succinic acid and butanediol in a molar ratio of 1:1.27 to a beating kettle, and adding a catalyst for beating together, wherein the catalyst is a mixture of zinc octoate and zinc chloride in a molar ratio of 1:2, and the amount of the catalyst added is 0.02% of the mass of PTA; beating for 30 minutes, and the obtained mixed slurry is placed in a slurry supply tank for internal circulation for standby use;

[0066] Among them, PTA is a white powder with a purity of 99.9% and a density of 1.51g / cm 3 ; Succinic acid is a white powder with a purity of 99.9%; butanediol is a colorless liquid with a purity of 99.9% and a boiling point of 225°C;

[0067] (2) pumping the mixed slurry obtained in step (1) into a first esterification kettle for esterification reaction, controlling the reaction temperature at 165° C., and controlling the flow rate of the mixed slurry entering the first esterification kettle at 160 kg / h, so that the liquid level in the first esterification kettle is maintained at 600 mm, and the esterification rate reaches 50%, thereby obtaining an esterified material;

[0068] (3) pumping the esterified material obtained in step (2) into a second esterification kettle for transesterification reaction, controlling the reaction temperature at 210° C., and the flow rate of the esterified material entering the second esterification kettle at 170 kg / h, so that the liquid level in the first esterification kettle is maintained at 600 mm, the transesterification rate reaches 98%, and an esterified melt is obtained;

[0069] (4) The esterified product melt obtained in step (3) is pumped into a melt pipeline through a metering pump, and the esterified product and the ester exchange product therein are mixed uniformly through a pipeline homogenizer. A polycondensation catalyst of 0.01% by weight of PTA is added upstream of the pipeline homogenizer through a syringe, and mixed uniformly with the esterified product melt through a pipeline homogenizer, and then enters an upflow pre-polycondensation kettle; the esterified product melt enters the upflow pre-polycondensation kettle for pre-polycondensation reaction, the melt temperature is controlled to be 245° C., the liquid level in the upflow pre-polycondensation kettle is maintained at 540 mm, and the reaction is carried out for 30 minutes under a vacuum degree of 1000 Pa to obtain a pre-polycondensation product;

[0070] The polycondensation catalyst is a butanediol solution of titanium chloride, wherein the mass fraction of titanium chloride is 70%; specifically, the titanium chloride is a white powder with a purity of 99.5%, and the butanediol solution of titanium chloride is a white liquid.

[0071] (5) The pre-polycondensation product obtained in step (4) enters a final polycondensation kettle for final polycondensation reaction, the melt temperature is controlled to reach 250° C., the liquid level in the final polycondensation kettle is maintained at 400 mm, and the reaction is carried out for 30 min under a vacuum degree of 50 Pa; the reaction product is tested at an online detection point, and after the intrinsic viscosity reaches 1.250 dL / g, a polyester melt that can be discharged is obtained;

[0072] (6) The polyester melt in step (5) is conveyed to a screw online adding device, wherein the screw extrusion temperature is 250°C, the screw speed is controlled at 300 rpm, and the screw aspect ratio is 70:1; auxiliary raw materials, including BIBP, polylactic acid and functional masterbatch, are added thereto through an online adding metering device, wherein the mass ratio of BIBP, polylactic acid and functional masterbatch is 1:1000:2000, and the total amount of auxiliary raw materials added is 15 kg / h; the molecular weight of polylactic acid is 250,000, and the melt index is 10 g / 10 min; the functional masterbatch uses PBST as a carrier, wherein the content of functional powder is 70%, and the functional powder includes nano talc and nano silicon dioxide in a mass ratio of 2:1; after mixing through the screw online adding device, extrusion is performed, and the extrusion rate is 295 kg / h (equivalent to a mass ratio of auxiliary raw materials to polyester melt of 1:18.7), thereby obtaining a special material for biodegradable polyester film;

[0073] (7) Using the biodegradable polyester film special material obtained in step (6) to blow film, a biodegradable polyester film is obtained, wherein the temperature of the film blowing machine is set to 140° C., 150° C., 160° C., the main screw speed is 400 rpm, the traction speed is 10 m / min, the blowing ratio is 4.5, and the film thickness is 20 μm.

[0074] Example 2

[0075] The difference between this embodiment and the above-mentioned embodiment 1 is that in step (1), succinic acid is replaced by adipic acid, and in step (6), the functional masterbatch uses PBAT as a carrier, and the other preparation steps and process parameters are the same as those in embodiment 1.

[0076] Example 3

[0077] (1) adding a mixture of PTA and succinic acid and butanediol in a molar ratio of 1:1.30 to a pulping kettle, and adding a catalyst for pulping together, wherein the catalyst is a mixture of zinc octoate and zinc chloride in a molar ratio of 1:2, and the amount of the catalyst added is 0.02% of the mass of PTA; pulping for 30 minutes, and the obtained mixed slurry is placed in a slurry supply tank for internal circulation for standby use;

[0078] Among them, PTA is a white powder with a purity of 99.9% and a density of 1.51g / cm 3 ; Succinic acid is a white powder with a purity of 99.9%; butanediol is a colorless liquid with a purity of 99.9% and a boiling point of 225°C;

[0079] (2) pumping the mixed slurry obtained in step (1) into a first esterification kettle for esterification reaction, controlling the reaction temperature at 165° C., and controlling the flow rate of the mixed slurry entering the first esterification kettle at 160 kg / h, so that the liquid level in the first esterification kettle is maintained at 600 mm, and the esterification rate reaches 50%, thereby obtaining an esterified material;

[0080] (3) pumping the esterified material obtained in step (2) into a second esterification kettle for transesterification reaction, controlling the reaction temperature at 210° C., and the flow rate of the esterified material entering the second esterification kettle at 170 kg / h, so that the liquid level in the first esterification kettle is maintained at 600 mm, the transesterification rate reaches 98%, and an esterified melt is obtained;

[0081] (4) The esterified product melt obtained in step (3) is pumped into a melt pipeline through a metering pump, and the esterified product and the ester exchange product therein are mixed uniformly through a pipeline homogenizer. A polycondensation catalyst of 0.01% by weight of PTA is added upstream of the pipeline homogenizer through a syringe, and mixed uniformly with the esterified product melt through a pipeline homogenizer, and then enters an upflow pre-polycondensation kettle; the esterified product melt enters the upflow pre-polycondensation kettle for pre-polycondensation reaction, the melt temperature is controlled to be 245° C., the liquid level in the upflow pre-polycondensation kettle is maintained at 540 mm, and the reaction is carried out for 30 minutes under a vacuum degree of 1000 Pa to obtain a pre-polycondensation product;

[0082] Wherein, the polycondensation catalyst is a butanediol solution of titanium chloride, wherein the mass fraction of titanium chloride is 80%; specifically, titanium chloride is a white powder with a purity of 99.5%, and the butanediol solution of titanium chloride is a white liquid.

[0083] (5) The pre-polycondensation product obtained in step (4) enters a final polycondensation kettle for final polycondensation reaction, the melt temperature is controlled to reach 250° C., the liquid level in the final polycondensation kettle is maintained at 400 mm, and the reaction is carried out for 30 min under a vacuum degree of 50 Pa; the reaction product is tested at an online detection point, and after the intrinsic viscosity reaches 1.250 dL / g, a polyester melt that can be discharged is obtained;

[0084] (6) The polyester melt in step (5) is conveyed to a screw online adding device, wherein the screw extrusion temperature is 250°C, the screw speed is controlled at 300 rpm, and the screw aspect ratio is 70:1; auxiliary raw materials, including BIBP, polylactic acid and functional masterbatch, are added thereto through an online adding metering device, wherein the mass ratio of BIBP, polylactic acid and functional masterbatch is 1:1000:2000, and the total amount of auxiliary raw materials added is 15 kg / h; the molecular weight of polylactic acid is 250,000, and the melt index is 10 g / 10 min; the functional masterbatch uses PBST as a carrier, wherein the content of functional powder is 70%, and the functional powder includes nano talc and nano silicon dioxide in a mass ratio of 2:1; after mixing through the screw online adding device, extrusion is performed, and the extrusion rate is 295 kg / h (equivalent to a mass ratio of auxiliary raw materials to polyester melt of 1:18.7), thereby obtaining a special material for biodegradable polyester film;

[0085] (7) Using the biodegradable polyester film special material obtained in step (6) to blow film, a biodegradable polyester film is obtained, wherein the temperature of the film blowing machine is set to 140° C., 150° C., 160° C., the main screw speed is 400 rpm, the traction speed is 10 m / min, the blowing ratio is 4.5, and the film thickness is 20 μm.

[0086] Comparative Example 1

[0087] This comparative example is used to prepare a biodegradable polyester film, wherein steps (1) to (4) are exactly the same as those in Example 1, and after step (4), the following steps are followed:

[0088] (5) The pre-polycondensation product obtained in step (4) enters a final polycondensation kettle for final polycondensation reaction, the melt temperature is controlled to reach 250° C., the liquid level in the final polycondensation kettle is maintained at 400 mm, and the reaction is carried out for 30 min under a vacuum degree of 50 Pa; the reaction product is tested at an online detection point, and after the intrinsic viscosity reaches 1.250 dL / g, it is extruded at an extrusion rate of 280 Kg / h to obtain a high-strength biodegradable PBST resin;

[0089] (6) The biodegradable PBST resin obtained in step (5) is uniformly mixed with BIBP, polylactic acid and functional masterbatch (the types of BIBP, polylactic acid and functional masterbatch and their respective addition ratios are the same as in Example 1), and film blowing is performed to obtain a biodegradable polyester film, wherein the temperature of the film blowing machine is set to 140°C, 150°C, 160°C, the main screw speed is 400rpm, the traction speed is 10m / min, the blowing ratio is 4.5, and the film thickness is 20 microns.

[0090] Comparative Example 2

[0091] This comparative example is used to prepare a biodegradable polyester film, wherein steps (1) to (3) are exactly the same as those in Example 1, and after step (3), the following steps are followed:

[0092] (4) The esterified melt obtained in step (3) is pumped into a melt pipeline via a metering pump, wherein the esterified product and the transesterified product are mixed uniformly via a pipeline homogenizer, and a polycondensation catalyst of 0.01% by weight of PTA is added upstream of the pipeline homogenizer via a syringe, and mixed uniformly with the esterified melt via a pipeline homogenizer, and then enters an upflow pre-polycondensation kettle; the polycondensation catalyst is a butanediol solution of titanium chloride, wherein the mass fraction of titanium chloride is 70%; BIBP, polylactic acid and functional masterbatch are also added to the upflow pre-polycondensation kettle (the types of BIBP, polylactic acid and functional masterbatch and their respective addition ratios are the same as those in Example 1) and mixed uniformly with the melt;

[0093] The esterified product melt was subjected to a pre-condensation reaction in an upflow pre-condensation reactor, the melt temperature was controlled to be 245°C, the liquid level in the upflow pre-condensation reactor was maintained at 540 mm, and the reaction was carried out for 30 minutes under a vacuum degree of 1000 Pa to obtain a pre-condensation product;

[0094] (5) The pre-polycondensation product obtained in step (4) enters a final polycondensation kettle for final polycondensation reaction, the melt temperature is controlled to reach 250° C., the liquid level in the final polycondensation kettle is maintained at 400 mm, and the reaction is carried out for 30 min under a vacuum degree of 50 Pa; the reaction product is tested at an online detection point, and after the intrinsic viscosity reaches 1.250 dL / g, it is extruded at an extrusion rate of 295 Kg / h to obtain a biodegradable PBST film blowing material;

[0095] (6) Using the biodegradable PBST film blowing material obtained in step (5) to blow film, a biodegradable polyester film is obtained, wherein the temperature of the film blowing machine is set to 140° C., 150° C., 160° C., the main screw speed is 400 rpm, the traction speed is 10 m / min, the blowing ratio is 4.5, and the film thickness is 20 μm.

[0096] Test Example 1

[0097] This test example conducted the following tests on the biodegradable polyester film special materials and film products prepared in the above embodiments and comparative examples.

[0098] Tensile strength: The tensile strength of the film product was tested using the ASTM D638 standard method. The greater the tensile strength, the stronger the rigidity of the product's molecular chain.

[0099] Elongation at break: The elongation at break of the film product was tested using the ASTM D638 standard method. The greater the elongation at break, the better the toughness of the product.

[0100] Hardness test: Test the biodegradable polyester film material according to ISO868-2003;

[0101] Melt index: The biodegradable polyester film special material is tested according to the standard GB / T3682-2000;

[0102] Hue b value test: The biodegradable polyester film special material is tested according to the standard GB / T14190-1993.

[0103] The test results of this test example are shown in Table 1 below.

[0104] Table 1 Performance test results

[0105] Tensile strength / MPa Elongation at break / % Hardness / A Melt index / g / 10min Hue b value Example 1 32 850 65 3.5 4 Comparative Example 1 25 600 65 6.0 6 Comparative Example 2 23 500 65 7.0 7 Example 2 31 900 70 3.0 4 Example 3 33 880 70 4.0 4

[0106] It can be seen that the biodegradable polyester film obtained in each embodiment has higher tensile strength and elongation at break, the special material for biodegradable polyester film has a lower melt index, is more suitable for film blowing, and has a lighter color, and the prepared film has relatively high strength.

[0107] At the same time, by comparing the test results of Example 1 and Comparative Example 1, it can be seen that the tensile strength and elongation at break of the biodegradable polyester film prepared in Example 1 are higher than those in Comparative Example 1. This indicates that the biodegradable polyester film special material obtained by the preparation method of the present invention can be directly blown, and the obtained film product has higher tensile strength and elongation at break, and the product quality is stable.

[0108] By comparing the test results of Example 1 and Comparative Example 2, it can be seen that the tensile strength and elongation at break of the biodegradable polyester film prepared in Example 1 are higher than those in Comparative Example 2. This indicates that the biodegradable polyester film special material obtained by the preparation method of the present invention is superior to the method of adding auxiliary raw materials such as functional masterbatch in the polymerization reaction stage. The melt index of the product obtained in Example 1 is less than 5g / 10min, indicating that the molecular weight of the polymer is high and suitable for making high-strength films.

[0109] Test Example 2

[0110] This test example investigates the effect of the amount of catalyst added in the esterification reaction stage on the quality of the obtained product during the preparation process. Specifically, referring to the preparation method in Example 1, only the amount of catalyst added in step (1) was changed, and the other preparation steps and process parameters were the same as in Example 1, and the mechanical properties of the obtained biodegradable polyester film special material were tested, and the results are shown in Table 2 below.

[0111] Table 2 Mechanical properties test results

[0112] Mass ratio of catalyst to PTA (%) Tensile strength / MPa Elongation at break / % 0.010 30 820 0.015 31 830 0.020 32 850 0.025 32 830 0.030 31 820 0.040 30 805

[0113] It can be seen from the above test results that with the increase in the amount of catalyst, the tensile strength and elongation at break of the obtained product show a trend of first increasing and then decreasing. When the amount of catalyst added is controlled to 0.01% to 0.03% of the mass of terephthalic acid, an elongation at break of not less than 820% can be achieved. In the optimal embodiment of the present invention, the amount of catalyst added is 0.02% of the mass of terephthalic acid, at which time the tensile strength and elongation at break can reach the highest level.

[0114] Test Example 3

[0115] This test example investigates the effect of the amount of polycondensation catalyst added in the pre-polycondensation reaction stage on the quality of the obtained product during the preparation process. Specifically, referring to the preparation method in Example 1, only the amount of polycondensation catalyst added in step (4) was changed, and the other preparation steps and process parameters were the same as in Example 1, and the mechanical properties of the obtained biodegradable polyester film special material were tested, and the results are shown in Table 3 below.

[0116] Table 3 Mechanical properties test results

[0117] Condensation catalyst relative to PTA mass ratio (%) Tensile strength / MPa Elongation at break / % 0.010 32 850 0.015 32 860 0.020 33 865 0.025 31 840 0.030 30 820

[0118] It can be seen from the above test results that with the increase in the amount of polycondensation catalyst, the tensile strength and elongation at break of the obtained product respectively show a trend of first slightly increasing and then slightly decreasing. When the amount of polycondensation catalyst added is controlled to 0.01% to 0.02% of the mass of terephthalic acid, an elongation at break of not less than 850% can be achieved, and the tensile strength is not less than 32MPa. Further, when the amount of polycondensation catalyst added is controlled to 0.015% to 0.020% of the mass of terephthalic acid, the elongation at break of the obtained product can be further increased to greater than or equal to 860%.

[0119] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment, it is not used to limit the present invention. Any technician familiar with this patent can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A method for preparing a biodegradable polyester film special material, characterized in that: The following steps are involved: (1) mixing a mixture of a dibasic acid and butanediol with a catalyst to obtain a mixed slurry, wherein the dibasic acid comprises terephthalic acid and an aliphatic dibasic acid, and the aliphatic dibasic acid is succinic acid or adipic acid; (2) subjecting the mixed slurry to an esterification reaction to obtain an esterified material; (3) the esterified material undergoes an ester exchange reaction to obtain an esterified melt; (4) the esterification product melt is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product; (5) subjecting the pre-polycondensation product to a final polycondensation reaction to obtain a polyester melt; (6) During the polyester melt discharging process, auxiliary raw materials are added online and extruded into granules to obtain a biodegradable polyester film special material, wherein the auxiliary raw materials include a micro-crosslinking agent, a stiffening agent and a functional masterbatch.

2. The method for preparing the biodegradable polyester film special material according to claim 1, characterized in that: In step (6), the polyester melt is subjected to a process of online addition of auxiliary raw materials and extrusion through a screw online adding device, wherein the screw extrusion temperature is 250-260° C., the screw speed is controlled to be 300-400 rpm, and the aspect ratio of the screw is 70-82:1; Preferably, the screw extrusion temperature is 255-260° C., the screw speed is controlled to be 300-350 rpm, and the aspect ratio of the screw is 75-82:

1.

3. The method for preparing the biodegradable polyester film special material according to claim 1 or 2, characterized in that: In step (6), the mass ratio of the micro-crosslinking agent, the stiffening agent and the functional masterbatch is 1:1000-1200:2000-2500, and the mass ratio of the total mass of the auxiliary raw materials to the polyester melt is 1-2:9-20; Preferably, the micro-crosslinking agent is a peroxide, including DCP or BIBP, preferably BIBP; Preferably, the stiffening agent is polylactic acid, the molecular weight of which is preferably 200,000 to 250,000, and the melt index is preferably 10 to 15 g / 10 min; Preferably, the functional masterbatch uses PBST or PBAT as a carrier, wherein the content of the functional powder is 70-75%; the melt index of the functional masterbatch is preferably 5-10g / 10min; the functional powder preferably comprises a mixture of nano-talc and nano-silicon dioxide in a mass ratio of 2-3:

1.

4. The method for preparing the biodegradable polyester film special material according to any one of claims 1 to 3, characterized in that: In step (1), a catalyst is added to the mixture of the dibasic acid and butanediol for pulping, and the pulping time is 20 to 30 minutes, preferably 20 to 25 minutes; Preferably, the dibasic acid and butanediol are added to a pulping kettle at a molar ratio of 1:1.27-1.30 for pulping; More preferably, in the dibasic acid, the molar ratio of terephthalic acid to aliphatic dibasic acid is 1:1.2-1.

3.

5. The method for preparing the biodegradable polyester film special material according to claim 4, characterized in that: The amount of the catalyst added is 0.01% to 0.03% of the mass of terephthalic acid, preferably 0.02%; Preferably, the catalyst is a mixture of zinc octoate and zinc chloride, wherein the molar ratio of zinc octoate to zinc chloride is 1:2 to 3; preferably 1:2 to 2.

5.

6. The method for preparing the biodegradable polyester film special material according to any one of claims 1 to 5, characterized in that: In step (2), the reaction temperature for the esterification reaction is 145 to 165° C., preferably 155 to 165° C.; after the esterification rate of the esterification reaction reaches 50% to 55%, preferably 52% to 55%, the ester exchange reaction of step (3) is carried out; Preferably, the mixed slurry is fed into the first esterification kettle for esterification reaction, and the flow rate of the mixed slurry entering the first esterification kettle is controlled at 160-180 Kg / h, preferably 165-175 Kg / h; the liquid level in the first esterification kettle is maintained at 600-800 mm.

7. The method for preparing the biodegradable polyester film special material according to any one of claims 1 to 6, characterized in that: In step (3), the reaction temperature for the transesterification reaction is 210 to 220° C., preferably 215 to 220° C.; after the transesterification rate of the transesterification reaction reaches 98% to 99.5%, preferably 98% to 99%, the pre-polycondensation reaction of step (4) is carried out; Preferably, the esterified material is fed into the second esterification kettle for ester exchange reaction, and the flow rate of the esterified material entering the second esterification kettle is controlled at 170-180 Kg / h, preferably 175-180 Kg / h; the liquid level in the second esterification kettle is maintained at 600-800 mm.

8. The method for preparing the biodegradable polyester film special material according to any one of claims 1 to 7, characterized in that: In step (4), the melt temperature is controlled to be 245-255° C., and the pre-polycondensation reaction is carried out under a vacuum degree of 1000-1250 Pa, and the reaction time is 30-50 min; the vacuum degree is preferably 1200-1250 Pa; Preferably, the esterification melt is fed into a pre-polycondensation kettle for pre-polycondensation reaction, and the liquid level in the pre-polycondensation kettle is controlled to be maintained at 540-560 mm; More preferably, before the esterified product melt enters the pre-polycondensation reactor, a polycondensation catalyst is added to the esterified product melt, and the amount of the polycondensation catalyst added is 0.01% to 0.02% of the mass of terephthalic acid; Further preferably, the polycondensation catalyst is a butanediol solution of titanium chloride, wherein the mass fraction of titanium chloride is 70% to 80%.

9. The method for preparing the biodegradable polyester film special material according to any one of claims 1 to 8, characterized in that: In step (5), the melt temperature is controlled to be 250-260° C., and the final polycondensation reaction is carried out under a vacuum degree of 50-100 Pa, and the reaction time is 30-40 min; the vacuum degree is preferably 50-80 Pa; Preferably, the pre-polycondensation product enters the final polycondensation kettle for final polycondensation reaction, and the liquid level in the final polycondensation kettle is controlled to be maintained at 400-500 mm; Preferably, the product of the final polycondensation reaction is detected online, and after the intrinsic viscosity reaches 1.250 to 1.350 dL / g, the polyester melt can be discharged in step (6).

10. A biodegradable polyester film special material, characterized in that: The biodegradable polyester film special material has a tensile strength of 30-35 MPa, an elongation at break of 800%-1000%, and a hardness of 60-70A; Preferably, the special material for biodegradable polyester film is prepared by the preparation method for the special material for biodegradable polyester film according to any one of claims 1-9.